Liquid Metal Enabled Biodevices. (4th May 2021) - Cole, Tim; Khoshmanesh, Khashayar; Tang, Shi-Yang
Abstract : Biodevices are crucial for monitoring vital physiological signals, managing chronic health conditions, developing artificial organs for assisting people with disabilities, and conducting various clinical and surgical procedures. However, existing biodevices are mostly composed of rigid components, which can cause discomfort to the user, whereas the high stiffness of implants is known to be the major cause of inflammation and scarring. Gallium‐based liquid metals are intrinsically soft and possess desirable properties, including low toxicity, high conductivity, and deformability, which make them ideally suited for developing soft, deformable, reconfigurable, and healable biodevices. Herein, recent advancements in the emerging field of liquid‐metal‐based biodevices are discussed. This includes a description of the properties of gallium‐based liquid metals which make them so distinct from conventional materials, a brief outline of various techniques devised for fabrication of liquid‐metal‐based devices/structures, and an overview of the diverse range of wearable or implantable liquid‐metal‐enabled biodevices. The outlook and challenges are also discussed. Abstract : Liquid metals show great potentials for use in biodevices due to their many beneficial properties, such as low toxicity, high conductivity, and deformability. Herein, unique properties of liquid metals are discussed, device fabrication methods are briefly outlined, and then many uses of liquid metals in biodevices are elaborated. Finally, a foresight is offered to exemplify future challenges.